Environmental chemistry course assisted problem-based learning in developing students’ higher-order thinking skills and characters. - Wildan Wildan; Supriadi Supriadi; Dwi Laksmiwati; Rizki Nur Analita (The University of Mataram, 2021)
Character development and higher-order thinking abilities are crucial in environmental chemistry courses because they can motivate students to care about the environment. Environmental chemistry courses can benefit from a problem-based learning approach. Students learn to think critically and analytically, as well as locate and use relevant learning resources, through problem-based learning. This was a quasi-experimental study that used a pre-test post-test design. The goal of this study was to describe how problem-based learning was implemented in environmental chemistry classes and how it influenced the development of higher-order thinking abilities and student personalities. Data was gathered through an essay test that required higher-order thinking skills, and students' personalities were determined through an inventory. ANOVA statistics were used to evaluate the data. The stages of concept presentation, presentation of factual problems in various forms, group discussions, and class discussions were used to implement problem-based learning in the Environmental Chemistry course; (2) problem-based learning can significantly improve students' higher-order thinking skills and characters; and (3) high-order thinking skills contribute significantly to character development.